Precarization via Digitalization? Work Arrangements in the On-Demand Platform Economy in Hungary and Slovakia - Kahancová, Marta; Meszmann, Tibor T.; Sedláková, Mária (Frontiers in Sociology, 2020)
The concept of precarity is increasingly used for an analysis of standard and non-standard (atypical) employment forms – yet among atypical employment forms, platform driven work is rarely included. This paper aims to fill this gap and provide a refined analytical framework for an evaluation of precarity in employment arrangements applicable to on-demand platform work. The legitimacy of such analytical framework is twofold. First, it allows identifying the dimensions if precarity in on-demand platform work. Second, it extends the understanding of how a general situation in the labour market connects to work precarity in on-demand platform work. The analytical framework is applied to evidence from two countries in Central and Eastern Europe - Hungary and Slovakia, where the rise of precarious employment went hand in hand with the rise of work via digital platforms. The central claim of the paper is that precarity in on-demand platform work is especially manifest in the dimensions of autonomy at work and of interest representation. Furthermore, digitalization enforces precarity while at the same time it mitigates labour market segmentation between standard and non-standard workers as distinct groups of workers.